ASSIMILATIVE GLOCALISM: DISSECTING POWER ASYMMETRIES THROUGH “THE HANDBOOK OF CULTURE AND GLOCALIZATION” (Glocalism: Journal of Culture, Politics and Innovation, 2025)
This paper delves deeply into the forces of globalization, leveraging The handbook of culture and glocalization (2022), edited by Victor N. Roudometof and Ugo Dessì, as both a resource and a subject of critique. While the handbook provides an expansive view of global influences across diverse sectors, it overlooks the power asymmetries embedded in glocalization. By examining theoretical gaps, conceptual ambiguities, and uneven engagements with global-local dynamics, this research uncovers a need for a more incisive framework to address the realities of power within globalization. To bridge this gap, the study introduces “assimilative glocalism”, a theoretical model designed to illuminate the strategic incorporation and subtle subordination of local elements within global structures. Through this, the paper presents a sophisticated balanced analysis of glocalization, revealing how integration often disguises underlying hierarchies. This research offers a pioneering perspective, re-envisioning glocalization as a complex interplay that simultaneously celebrates and constrains diversity. This contribution not only enriches the discourse but also enhances the theoretical tools available for studying globalization.
Keywords: authority; hegemony; inequality; sustainability; asymmetric power